Constraints on the source of ions in the Jianhe hot springs in Guizhou Province, China by water-rock interaction experiments - Xiangheng Pu; Li Zhou; Zhengshan Chen; Wenge Zhou (PLoS ONE, 2025)
Due to the lack of experimental studies, the effect of water-rock interactions on the hydrochemical characteristics of hot springs within belted reservoir remains poorly understood. To solve this issue, we analyzed the hydrochemical characteristics of the hot springs and the geochemical features of the reservoir rocks in the Jianhe hot springs in Guizhou province, SW China. All water sample analyses adhered to the China analytical procedures (GB 8538−2022), then carried out water-rock interacting experiments with representative reservoir rocks (e.g., metamorphosed tuff, metamorphosed quartz sandstone, and slate) under varying reaction time, temperature, and pH conditions. The results indicate that the concentration of dissolved ions in the solution increased with time, then gradually stabilized, reaching dynamic equilibrium around 35 days. Higher temperatures facilitated the leaching of K+, Na+, and H2SiO3, meanwhile reduced the leaching of Ca2+ and Mg2+. However, both Ca2+ and Mg2+ in the solution showed a pronounced response to pH changes from 4 to 10, whereas the K+, Na+, and H2SiO3 concentrations were less sensitive to pH changes. In particular, under experimental conditions corresponding to the reservoir (90°C), the Ca2+, concentrations as leached from metamorphosed tuff agreed well with the hydrochemical data in Jianhe hot springs, which are significantly lower than those in the solutions interacted with quartz sandstone or slate, and indicate that metamorphosed tuff should be the primary sources for K+, Na+, Ca2+, Mg2+ and H2SiO3 in the hot springs.